Natural and experimental cold exposure in adulthood increase the sensitivity to future stressors in a free‐living songbird. (30th July 2022) - Vitousek, Maren N.; Houtz, Jennifer L.; Pipkin, Monique A.; Chang van Oordt, David A.; Hallinger, Kelly K.; Uehling, Jennifer J.; Zimmer, Cedric; Taff, Conor C.
Abstract: As the global climate shifts, many species are imperilled by changing thermal regimes. Despite rising global temperatures, some populations must contend with more frequent or extreme cold. In these populations, the ability to cope with cold may be an important determinant of fitness. Experiments in captive animals have shown that extreme cold or rapid temperature declines typically elicit an increase in glucocorticoid hormones (mediators of the stress response); however, it is not known whether free‐living adults, which may be better at buffering the effects of cold, show a similar response to ecologically relevant thermal challenges. The effects of cold on the sensitivity to future challenges are also poorly understood. Using targeted manipulations of nest temperature in free‐living tree swallows Tachycineta bicolor and a long‐term dataset (2, 888 samples; 8 years), we tested the relationship between cold exposure and glucocorticoid levels in adults. Both natural and experimental cold exposure altered glucocorticoid regulation. This manifested primarily in terms of an upregulation in the sensitivity to future challenges (stress‐induced levels). Experimental cold exposure also increased the initial speed and duration of the acute stress response. Analyses of the long‐term dataset found that baseline glucocorticoids were higher in cold conditions; however, the magnitude of this effect was weak. A sliding window analysis revealed differences in the timeline over which temperature best predicted baseline and stress‐induced glucocorticoids. Although unpredictability is often regarded as a defining factor of stressors, we found that recent ambient temperatures better predicted circulating corticosterone than measures of thermal unpredictability, including the degree of recent temperature change and negative prediction error (the difference between experienced temperatures and long‐term averages). Together, these results suggest that thermally induced increases in the sensitivity to future challenges may prime individuals to respond more strongly or rapidly to worsening conditions, or to subsequent challenges of a different type, without incurring the costs that can result from substantial elevations in baseline glucocorticoids. This kind of preparatory response could be adaptive; however, an increased sensitivity to other challenges could also represent an overlooked cost of changing thermal regimes. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.